2015
DOI: 10.1161/circimaging.115.004045
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography and Virtual-Histology Intravascular Ultrasound

Abstract: T he ultimate goal of studies such as the one by Brown et al 1 in this issue of Circulation: Cardiovascular Imaging is to provide the clinician with a diagnostic tool that identifies high-risk plaques prospectively to treat and prevent acute events. This tool must have a high positive predictive value and negative predictive value in the clinical setting and not require specific expertise or core-laboratory analysis to determine whether a plaque is vulnerable and should be treated pre-emptively-a yes/no, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The direct comparison between VH-IVUS and OCT by Brown et al found that both VH-IVUS and OCT could identify advanced coronary plaques and that combined VH-IVUS/OCT was better than either alone [33]. However, OCT has a low signal penetration through lipid or necrotic core, and cannot adequately acquire images of the whole vessels with large lumen diameter or large necrotic core [29, 34]. This presents a problem for imaging of large vessels including vein grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct comparison between VH-IVUS and OCT by Brown et al found that both VH-IVUS and OCT could identify advanced coronary plaques and that combined VH-IVUS/OCT was better than either alone [33]. However, OCT has a low signal penetration through lipid or necrotic core, and cannot adequately acquire images of the whole vessels with large lumen diameter or large necrotic core [29, 34]. This presents a problem for imaging of large vessels including vein grafts.…”
Section: Discussionmentioning
confidence: 99%
“…This presents a problem for imaging of large vessels including vein grafts. The presence of macrophages, foam cells, microcalcifications, or hemosiderin, often co-existent with the necrotic core, could be adverse to accurate OCT assessment of lipidic plaque [29, 34]. VH-IVUS, which has become clinically available, can assess both plaque morphology and tissue characteristics using spectral and amplitude analysis of backscattered radiofrequency ultrasound signal.…”
Section: Discussionmentioning
confidence: 99%
“…A lipid plaque was defined as a low signal region with diffuse border and a maximum arc of lipid ≥90°. This maximum arc is an excellent discriminator of fibroatheroma and together a fibrous cap thickness ≤85 µm identifies thin‐cap fibroatheroma when combined with a fibrous cap thickness ≤85 µm . Measurements of fibrous cap thickness were not possible, as OCT recordings were performed after stenting.…”
Section: Methodsmentioning
confidence: 99%
“…A lipid plaque was defined as a low signal region with diffuse border and a maximum arc of lipid ≥ 90°. This maximum arc is an excellent discriminator of fibroatheroma [ 19 ] and together a fibrous cap thickness ≤85 μm identifies thin-cap fibroatheroma when combined with a fibrous cap thickness ≤85 μm [ 20 ]. Meassurements of fibrous cap thickness were not possible, as OCT recordings were performed after stenting.…”
Section: Methodsmentioning
confidence: 99%